Forensic child psychology working in the courts and clinic - Fanetti, Matthew; O'Donohue, William T.; Happel, Rachel N.; Daly, Kresta (Wiley, 2015)
"A guide to working effectively with children in the criminal justice system. Uniquely designed to train psychology, criminology, and social work students to work with children in the criminal justice system--both in the courtroom and as clinical clients--Forensic Child Psychology presents current research and practice-based knowledge to improve the judicial and child welfare systems. Authors Matthew Fanetti, William T. O'Donohue, Rachel N. Happel, and Kresta N. Daly bring their combined expertise in child psychology, forensic interviewing, and criminal prosecution to bear on the process of obtaining accurate information from children involved in legal proceedings, preparing professionals to work with: Children who are victims of crime Children who are perpetrators of crime Children who are witnesses of crime The book also covers related topics, including mandated reporting, the structure of juvenile justice and advocacy systems, and contains sidebars, summaries, glossaries, and study questions to assist with material mastery.This is an excellent resource for students of child psychopathology in psychology, social work, nursing, and criminal justice at the graduate and late undergraduate stage of their educations"--Provided by publisher.